Principal Leadership Transformation: Improving Teacher Readiness For Inclusive Education In Societi 5.0 Era - Zawawi, M. Ilmil; Zaini, Zainuddin Al Haj; Fauzi, Imron (Center of Language and Cultural Studies, 2024)
Principal leadership is key in steering educational institutions towards standards of excellence that are relevant to the times. Inclusive education is the main focus in the Era Society 5.0, where every student, including those with special needs, has equal opportunities. Principals need to have effective leadership, not only administrative, but also able to create an inclusive school culture and encourage collaboration between all stakeholders. Literature study became the research method in exploring information related to principal leadership, inclusive education and educational challenges in the Era of Society 5.0. The results showed that the principal's collaborative leadership positively influenced teacher performance, while the role of Islamic boarding schools was recognized as a forum for religious and social education. In facing Society 5.0, literacy skills, including data literacy, technology literacy, and human literacy, are crucial. Analysis of the results shows that school principals play an important role in facing the changing times and advancing education according to the needs of society.